A simple theory of structural transformation - Max Gillman (Cardiff University, Cardiff Business School, 2011)
The paper presents a theory of the industrial transformation amongst sectors using endogenous growth theory. Allowing only a slight upward trend in the productivity of the human capital sector, combined with ascending degrees of human capital shares of sectoral output, in say, agriculture, manufacturing and services, output gradually shifts relatively over time from agriculture to manufacturing and to services. Abstracting from international trade theory, sectors intensive in the factor that is becoming relatively more plentiful find their relative outputs expanding. Adding more sectors of greater human capital intensity causes labor time to decrease within each sector, as shown for agriculture, and in general for any number of sectors.
Keywords: E25; F11; J24; O14; 330; Human Capital Intensity; Sectoral Allocation; Labor Shares; Secular Endogenous Growth; Strukturwandel; Humankapital; Produktivität; Branchenentwicklung; Theorie